The Effect of Marketing Strategy and Promotion Activities on Marketing Performance of Ritail Business - Suhandi Suhandi (Almana : Jurnal Manajemen dan Bisnis, 2020)
Today's retail industry is experiencing rapid development along with technological advances and the construction of supporting facilities. Tangerang is one of the cities that is part of the Banten Province which is growing rapidly. rapid modernization affected the city, making it one of the largest cities in Indonesia. This study aims to determine the effect of marketing strategies and promotional activities on the marketing performance of Retail Business Actors in Mall Plaza Bintaro. The method used was explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study the marketing strategy has a significant effect on marketing performance by 38.2%, the hypothesis test obtained t count> t table or (7.625> 1.989). Promotional activities have a significant effect on marketing performance by 39.9%, the hypothesis test obtained t count> t table or (7.892> 1.989). Marketing strategy and promotion activities simultaneously have a significant effect on marketing performance by 48.9%, the hypothesis test is obtained F count> F table or (44.464> 2,700)